Complex thought and knowledge management: basic factors of educational quality - Balbín de la Cruz, María (2022)
The scientific method, a basic instrument of scientific research, indicates that an inquisitive study of this level has its genesis in the determination of a problem, for this specific case the problem was the little information that is had about the two variables, knowing this situation and to continue with the coherent sense of the research, the objective was defined, which literally says: Explain complex thinking and knowledge management as basic factors to promote educational quality. The convenient basic method used was the hermeneutic one that facilitated knowing, understanding and explaining the various theories fundamentally included in the theoretical framework. The type of research is basic, because it follows a theoretical framework that aims to increase philosophical knowledge. Arriving later at  the result that is expressed as follows: First: Complex thinking explores ways of thinking based on the complexity of the world, articulating global knowledge based on singular knowledge and vice versa, under Morin's precepts: complex thinking is an "operator of the thought that relates”; second, complex thinking and knowledge management are basic factors for promoting educational quality.